1984
DOI: 10.1007/bf01801767
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of collagen in aspartylglycosaminuria: Urinary excretion of hydroxyproline

Abstract: Aspartylglycosaminuria (AGU) is a lysosomal storage disorder of glycoprotein degradation characterized by severe mental retardation and connective tissue alterations. We have previously described low collagen production in skin fibroblast cultures from AGU patients. In the present work we showed that the urinary excretion of hydroxyproline (total, non-dialysable and free hydroxyproline as indicators of collagen metabolism) was reduced in young AGU patients in comparison with age-matched controls. In adult pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The villi lamina propia core is mainly composed of connective tissue (Udenfriend 1966); therefore damage to ileal villi and its connective tissue could result in collagen leakage into ileal lumina and degradation into constituent components like T4HP. Breakdown of collagen would explain T4HP in urine of A mice consistent with rat and human studies reporting increased urinary T4HP in collagen breakdown from other causes (Näntö-Salonen et al 1984, Prockop and Sjoerdsma 1961; Anasuya and Rao 1970). T4HP may serve as a useful marker of intestinal necrosis in NEC in preterm infants and in other childhood inflammatory bowel diseases.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The villi lamina propia core is mainly composed of connective tissue (Udenfriend 1966); therefore damage to ileal villi and its connective tissue could result in collagen leakage into ileal lumina and degradation into constituent components like T4HP. Breakdown of collagen would explain T4HP in urine of A mice consistent with rat and human studies reporting increased urinary T4HP in collagen breakdown from other causes (Näntö-Salonen et al 1984, Prockop and Sjoerdsma 1961; Anasuya and Rao 1970). T4HP may serve as a useful marker of intestinal necrosis in NEC in preterm infants and in other childhood inflammatory bowel diseases.…”
Section: Resultssupporting
confidence: 77%
“…Correspondingly, the p-value for 14 out of the 15 T4HP-associated buckets were 10 −4 or smaller. T4HP is a breakdown product of collagen (Näntö-Salonen et al 1984) found largely in connective tissue (Udenfriend 1966). The villi lamina propia core is mainly composed of connective tissue (Udenfriend 1966); therefore damage to ileal villi and its connective tissue could result in collagen leakage into ileal lumina and degradation into constituent components like T4HP.…”
Section: Resultsmentioning
confidence: 99%